Clozapine-Induced Somnambulism in a 55-year-old Lady with Psychotic Depression: A Case Report - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Sleep walking disorder or somnambulism is a parasomnia that occurs in non-rapid eye movement sleep (NREM) characterized by an individual arising from bed and ambulating without fully awakening. It is known to be associated with multiple medications and has been reported with atypical antipsychotics. Here, we report a case of sleep walking induced by clozapine; before this, there have only been two reported cases of clozapine induced somnambulism.